Conceptualisations of and responses to plagiarism in the South African higher education system - Mphahlele, Martha Matee (Amanda) (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2020)
Violations of academic integrity are a cause for concern in universities around the world and plagiarism is one of the most significant examples of these academic integrity issues with which universities are grappling . The approach taken to managing plagiarism depends to a large extent on the understanding of the phenomenon within institutions. This study investigated how plagiarism is conceptualised and responded to in the South African Higher Education system and how this impacts on teaching and learning. Data was collected from 25 out of the 26 South African public universities; the missing university had just been established and did not yet have policies or processes in place. The data was primarily in the form of documents known in these institutions as 'plagiarism policies', along with a wealth of other related policies and reports. This was supplemented by interviews as a means of verifying the document analysis with seven plagiarism committee members from across the three institutional types in South Africa, namely: traditional universities, comprehensive universities, and universities of technology. Using Bhaskar's (2008) critical realism as a metatheory and Archer's (1995) social realism as both a substantive theory and analytical framework, the experiences and events of plagiarism management were critically examined. Critical realism consider s these experiences and events at the level of the e mpirical and the actual , in order to identify the mechanisms at the l evel of the r eal from which these emerge. Social realism argues that when undertaking such an analysis in the social world, this entails identifying the emergent properties of both the parts (structure and culture) and people (agents). Therefore, the data was analysed using Archer's analytical dualism to identify structural, cultural and agential mechanisms shaping the understanding of plagiarism and the practices associated with managing the phenomenon. The study found that dominant in the sector was an un derstanding of plagiarism as always being an intentional act, with implications for teaching and learning practices, which then focused on identifying and punishing incidents of plagiarism in student writing. A legal discourse was found to permeate the universities' plagiarism management systems, such that most procedures replicated the legal framework. This was seen to undermine the identity of universities as teaching and learning spaces and of students as novice members of the disciplinary fields. The study further highlighted that due to plagiarism being perceived as an intentional act, punishment in almost all universities is prioritised as the key means of attending to plagiarism in the se institutions. This emerged as a structural constraint to students' acquisition of academic writing norms. Such understandings and approaches were seen to be complementary to the risk-aversion of many institutions in a globalised era of university rankings. As increased bureaucracy has been put in place to attend to incidents of plagiarism, including obligatory reporting thereof, an unintentional consequence emerged, where it was at times simpler for academics to ignore incidences of plagiarism than to act on them. Turnitin was frequently referred to across the data as the preferred text - matching tool, but Turnitin together with other text-matching tools , was often used in a way that complemented the understanding of plagiarism as always being an intentional act. The stu dy found that text - matching software was largely misunderstood to be plagiarism software, where the similarity index was perceived to be a measure of plagiarism. This led to an understanding that students needed to paraphrase texts in order to avoid detect ion by the program me, and this may inadvertently encourage plagiarism , as students are taught to write towards the software. The research found that in those instances where educational responses to plagiarism were in place, they often demonstrated a lack of understanding of academic literacies development and the extent to which norms of knowledge production are disciplinary specific. Most (but not all) of the data about educational responses focused on add-on workshops and the signing of a declaration form, indicating that the student has not plagiarised. The workshops were seen to emphasise technical skills, such as the punctuation norms of referencing, and were often offered in a generic format by people outside of the target disciplines. These workshops were found to ignore the connection between the technical skills of referencing and the norms of knowledge construction, with a potential deleterious effect on the development of authorial identity. Finally, the data showed a few instances where particular institutions acknowledged that plagiarism occurs along a continuum, where on one side is intentional plagiarism associated with cheating and requiring punishment, and on the other side is unintentional plagiarism, which is understood to require an educational response , and was seen to emerge from either a lack of understanding of academic literacy norms , or from negligence. Literacy development with regard to taking on the norms of knowledge-making in the academy was seen to be a complex and lengthy process that was fundamental to educational endeavours of facilitating epistemological access, while cases of negligence were seen to be mainly caused by technical oversight rather than a lack of access to the relevant knowledge production norms. The study concludes by arguing that cases of intentional plagiarism require quick and appropriate punishment, but that there also needs to be an institution-wide understanding that unintentional plagiarism often emerges from students failing to access the specific knowledge-making norms of the discipline. There is thus a need for academics to be aware of the complexities related to taking on literacy practices, and who also understand the role of feedback in this process. But it ought not to be assumed that academics would have such insights simply by virtue of their expertise in the discipline. These academics need to have carefully constructed staff development support, as they take on such pedagogical approaches. The study argues that the dominant conceptualisation of plagiarism in the domain of culture as an intentional act and the complementary policies and processes in the domain of structure as focusing on detecting and punishing incidents of plagiarism, fail to address plagiarism in appropriate educational ways.
Keywords: Plagiarism; Plagiarism -- Prevention -- South Africa; Education, Higher -- Moral and ethical aspects; Education, Higher -- South Africa; Cheating (Education) -- South Africa; College students -- Legal status, laws, etc. -- South Africa; College discipline -- South Africa